Lutheran perspectives on interfaith relations: Theological trajectories of study processes in the Lutheran communion. Issue 2 (3rd June 2019) - Sinn, Simone
Abstract: The global Lutheran communion has been engaged in theological reflection on interreligious relations for several decades. In the 1960s, the Lutheran World Federation embarked on theologically reflecting on its relations to the Jewish people. This led to a critical assessment of Luther's writings on Jews. 1984, the LWF established a desk to engage theologically with religious pluralism. Starting off from a theology of religions' approach the engagement of the global communion has become more contextual, dialogical, and collaborative over the years. This has led to a dialogical public theology which affirms dialogue and theology as sisters in a critical‐constructive engagement with one's own and other communities. Raising epistemological and theological questions in dialogue in view of religious actors' public accountability can help to prevent faith from mutating into ideology or manifesting itself as idolatry.